6 - (2 x 7) - (3 x (-9)) = 19
Starting with the number 4, applying the rule of multiplying by 2 and then subtracting 3 gives the following sequence: 4, 5, 7, 11, 19, 35. This pattern can be calculated as follows: 4 x 2 - 3 = 5, 5 x 2 - 3 = 7, 7 x 2 - 3 = 11, 11 x 2 - 3 = 19, 19 x 2 - 3 = 35.
Either 1 x 133, or 7 x 19.
19
103
7 + 3 x 4 =7 + 12 = 19
133 = 7 x 19 54 = 2 x 3 x 3 x 3 LCM = 2 x 3 x 3 x 3 x 7 x 19 = 7182
3078 = 2 x 3 x 3 x 3 x 3 x 19
399 = 3 x 7 x 19 1330 = 2 x 5 x 7 x 19 gcf = 7 x 19 = 133
399 = 3 * 7 * 19
If: 3x+7 = 19 Then: 3x = 19-7 And: 3x = 12 So: x = 12/3 = 4
2 x 3 x 3 x 3 x 7 x 19 = 7182
3 x 7 x 19 = 399
Factor them. 3 x 7 = 21 3 x 11 = 33 3 x 19 = 57 Multiply the highest amount of each factor. 3 x 7 x 11 x 19 = 4389
6 - (2 x 7) - (3 x (-9)) = 19
19 - 7 = 3x Simply subtract 19 from 7 on the left side:12 = 3xSo you need 3 of x to get 12...sounds a bit like 3 times 4, doesn't it? After dividing both sides by 3, you can see that this is true:12/3 = x4 = xSo, x is equal to 4.
2 x 3 x 7 x 19 x 113 = 90174